Engaging Caregivers in Health-Related Housing Decisions for Older Adults With Cognitive Impairment: A Cluster Randomized Trial. (16th May 2019) - Adekpedjou, Rhéda; Stacey, Dawn; Brière, Nathalie; Freitas, Adriana; Garvelink, Mirjam M; Dogba, Maman Joyce; Durand, Pierre J; Desroches, Sophie; Croteau, Jordie; Rivest, Louis-Paul; Légaré, France
Abstract: Background and Objectives: Informal caregivers are rarely as involved as they want to be in the housing decisions of cognitively impaired older adults. Lack of awareness of available options and their benefits and risks may lead to decisions that do not reflect older adults' preferences, and to guilt and regret. We assessed the effect of training home care teams in interprofessional shared decision-making (SDM) on the proportion of caregivers who report being active in this decision. Research Design and Methods: In a two-arm pragmatic cluster randomized trial with home care teams working in health centers in the Province of Quebec, we randomized health centers to receive training in interprofessional SDM (intervention) or not (control). Eligible caregivers had made a housing decision for a cognitively impaired adult aged 65 years or older who was receiving services from a home care team. The primary outcome was the proportion of caregivers reporting an active role in decision making. We performed intention-to-treat multilevel analysis. Results: We consecutively enrolled a random group of 16 health centers and recruited 309 caregivers, among whom 296 were included in the analysis. In the intervention arm, the proportion of caregivers reporting an active role in decision making increased by 12% (95% CI −2% to 27%; p = .10). After removal of an influential cluster outlier, the proportion increased to 18% (95% CI: 7%–29%; p < .01). Discussion and Implications: Training home care teams in interprofessional SDM increased caregiver involvement in health-related housing decisions for cognitively impaired older adults.